Stateczność Pozornie Niesztywnej Powłoki Ramowo-Kratowej Ściskanej Siłą Osiową - W. Gutkowski (Engineering Transactions, 1963)
The object of the present considerations is a regular bar system shown by Fig. 1. In order to avoid two rough simplifications the difference calculus is used throughout the paper. The resolving functions are given for the most frequent case of square shell. From these functions it follows that the form of stability loss for axial compression is a flexural–torsional form.